CLAPPING, VIBRATING, POSTURAL DRAINAGE, AND EFFECTIVE COUGH AS MEASURES TO RESOLVE THE PROBLEM OF INEFFECTIVE AIRWAY CLEARANCE IN PATIENTS WITH BRONCHITIS - Wahyu Pranoto; Difran Nobel Bistara; Umdatus Soleha; Priyo Mukti Pribadi Winoto (Nurse and Holistic Care)
Introduction: Bronchitis is characterized by excessive sputum production due to an infection in the bronchi. In patients with bronchitis, it can cause nursing problems in the form of ineffective airway clearance. Ineffective airway clearance is the inability to clear the airway which is characterized by changes in frequency, pattern, and breath sounds.